Application of Ultrasonic Bone Curette in Endoscopic Endonasal Skull Base Surgery: Technical Note - Rastelli, Milton M., Jr.; Pinheiro-Neto, Carlos D.; Fernandez-Miranda, Juan C.; Wang, Eric W.; Snyderman, Carl H.; Gardner, Paul A. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background Endoscopic endonasal surgery (EES) of the skull base often requires extensive bone work in proximity to critical neurovascular structures.Objective To demonstrate the application of an ultrasonic bone curette during EES.Methods Ten patients with skull base lesions underwent EES from September 2011 to April 2012 at the University of Pittsburgh Medical Center. Most of the bone work was done with high-speed drill and rongeurs. The ultrasonic curette was used to remove specific structures.Results All the patients were submitted to fully endoscopic endonasal procedures and had critical bony structures removed with the ultrasonic bone curette. Two patients with degenerative spine diseases underwent odontoid process removal. Five patients with clival and petroclival tumors underwent posterior clinoid removal. Two patients with anterior fossa tumors underwent crista galli removal. One patient underwent unilateral optic nerve decompression. No mechanical or heat injury resulted from the ultrasonic curette. The surrounding neurovascular structures and soft tissue were preserved in all cases.Conclusion In selected EES, the ultrasonic bone curette was successfully used to remove loose pieces of bone in narrow corridors, adjacent to neurovascular structures, and it has advantages to high-speed drills in these specific situations.
Keywords: endoscopic endonasal; skull base; bone removal; ultrasonic bone curette